The significant characteristics of corticobasal syndrome - Parthimos, Theodore P.; Schulpis, Kleopatra H. (Annals of Research Hospitals, 2019)
Corticobasal syndrome (CBS) is a rare neurodegenerative disorder. Mutation in the microtubule associated protein tau (MAPT) has been presented in patients with CBS. Also, a mutation in the gene that encodes progranulin (PGRN) is frequently observed in CBS patients. Patients with this syndrome present predominantly dementia findings. This syndrome is associated with various clinical and laboratory characteristics which give the opportunity to differentiate among the other dementia syndromes. The aim of this study was to described symptoms and signs of the CBS and its confirmation with mutation analysis of the related genes. Patients with CBS commonly present Parkinsonism like syndrome/ Parkinson disease findings such as akinesia, rigidity and dystonia. Myoclonus, limb apraxia and alien limb phenomena are also included in the clinical presentation of the disease. Most patients also complained because of agraphia, difficulties in spontaneous speech and both single-word and sentence repetition inability. Magnetic resonance imaging (MRI) present damage to the primary motor cortex, inferior parietal, left supplementary motor area and basal ganglia. Levodopa, benzodiazepines and anticholinergic agents are commonly used for the therapeutic process of the syndrome. Even though a tiny amelioration of patient’s symptoms is usually observed, the outcome is very poor. CBS is a rare dementia disorder which is associated with symptoms commonly found in Parkinsonism like syndrome/ Parkinson disease plus dementia. The response of the therapeutic treatment is very disappointing.